Dual‐blockchain‐based P2P energy trading system with an improved optimistic rollup mechanism. Issue 4 (27th May 2022) - Yu, Teng; Luo, Fengji; Pu, Canglong; Zhao, Zehua; Ranzi, Gianluca
Abstract: Blockchain technology has been recognised as a promising technology for supporting Peer‐to‐Peer (P2P) energy trading—an emerging paradigm in which energy trading is performed directly between end energy customers. The state‐of‐the‐art blockchain designs for P2P energy trading can only support less compute‐intensive energy trading tasks and/or rely on the set up of a long challenge time to ensure correctness of transactions, which restricts the systems' scalability and applicability in the diverse P2P energy trading applications. This paper proposes a new dual‐blockchain system for P2P energy trading. The system consists of a primary blockchain and a secondary blockchain. The primary blockchain is mainly responsible for storing the data of P2P energy trading transactions while the compute‐intensive tasks (e.g. pricing and transaction verification) are executed in the secondary blockchain. An Improved Optimistic Rollup (IOR) mechanism is proposed to facilitate the co‐operation of the dual blockchains. Through a specific 'executor‐validator' mechanism and a group of specific smart contracts with different functions, the IOR mechanism can effectively accommodate the dual blockchains to execute the P2P energy trading transactions in a computational efficient manner while ensuring the correctness and security of the transactions. A prototype of the proposed system is implemented on Fisco Bcos and Alibaba Cloud and comprehensive simulations are conducted to validate the proposed system.